Refugee Crisis and Migrations at the Gates of Europe: Deterritoriality, Extraterritoriality and Externalization of Border Controls - Alejandro Del Valle Gálvez (Paix et Sécurité Internationales, 2019)
The refugee crisis has shaped a new perception of the migration reality in Europe. The ramifications of its impact on European integration are visible and enduring. The EU’s response has included a certain strategic perspective, albeit weighed down by an excess of eurocentrism and a security perception that does not take third countries’ interests into balanced account. The major economic effort being made supports a far-reaching strategy, only now beginning to be outlined, to promote economic development in the countries of origin and transit of migrants. Additionally, issues such as the monitoring of respect for migrants’ human rights have not yet been suitably globally defined in this strategy.